Characterising biomolecular interactions and dynamics with mass photometry - Asor, R; Kukura, P (Elsevier, 2022)
We review recent advances in our ability to characterise biomolecular structure, interactions and associated dynamics by mass photometry (MP), the label-free detection and mass measurement of individual biomolecules in solution. Molecular counting and identification provides direct access to relative abundance, and thereby affinities, while associated dynamics yield on- and off-rates. The molecular resolution afforded by MP enables these measurements as a function of stoichiometry and assembly at equilibrium, as opposed to the majority of existing solution-based methods. Together with future improvements in terms of assays and technological performance, MP is likely to provide mechanistic details of complex biomolecular processes.